The Impact of Alleged Israeli Genocide in Palestine: An Analytical Review - Ghanim ismail (Global Writing Academica Researching & Publishing, 2024)
The Israeli-Palestinian conflict, a deeply rooted and prolonged struggle, has been the subject of extensive international debate and scrutiny. This article delves into the contentious allegations of genocide perpetrated by Israel against the Palestinian population. By examining the historical context, political dynamics, humanitarian impact, and international responses, this study seeks to provide a nuanced and comprehensive analysis of the situation. Beginning with a detailed overview of the term